DAMPAK KOPERASI TERHADAP KINERJA USAHATANI DAN KESEJAHTERAAN PETANI PADI DI PROVINSI LAMPUNG - , DYAH ARING HEPIANA LESTARI; , Prof. Dr. Ir. Masyhuri ([Yogyakarta] : Universitas Gadjah Mada, 2012)
The objectives of this study were to analyze : (1) business activity provided by koptan/KUD in rice production centers, (2) decision-making process of rice farmers to become a member of Koptan/KUD and the factors affecting it, (3) the participation level of koptan/KUD members and the factors affecting it, (4) the impact of farmers membership in koptan/KUD on the rice farming performance (production, income, technical efficiency, allocatiye efficiency, and economic efficiency), (5) the transaction costs incurred, the economic benefits received, and non-economic benefits felt by Koptan/KUD members, (6) the impact of the farmers membership in koptan/KUD on the structure of household income, and (7) the impact of farmers membership in koptan/KUD on the welfare and its distribution. This study was conducted in three districts having the highest number of koptan and KUD as well as the dominant producers of rice in Lampung Province. The three districts were Central Lampung, East Lampung, and South Lampung. Six koptan and six KUD from the three districts were selected as samples. 233 rice farmers consisting of members and non-members of koptan/KUD were also selected as samples. Data were analyzed using descriptive methods, probit model, multiple linear regression model with OLS and SUR methods, Cobb- Douglas production function, profit function, the average of different test (t-test and ANOVA), Importance-Performance Analysis, and the Gini Ratio. The results showed that: (1) the business activities of koptan/KUD has not been as expected, (2 the decision-making process in a membership of Koptan/KUD goes as follows: searching and collecting data information, figuring out some alternatives, and making decisions. Farming experience, socialization and education about cooperatives, farmers' willingness to cooperate, and the SHU received by koptan/KUD members influenced farmers' decisions, (3) the members participation in the RAT was moderate, affected by formal and nonformal education, farming experience, the length of membership in cooperative, SHU, reimbursement of transport expenses for attending RAT, food provided at RAT, and types of cooperatives